Aluminum nitride sintered body and its manufacturing method
The aluminum nitride sintered body with enhanced thermal conductivity and reduced warpage is achieved through a specific manufacturing process involving aluminum nitride and yttrium oxide, addressing the challenges of deformation and warping in conventional methods.
Patent Information
- Application Number
- JP2024035702
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-03-08
- Publication Date
- 2025-03-19
- Estimated Expiration
- 2044-03-08
AI Technical Summary
Conventional sintered aluminum nitride bodies require high-temperature sintering in a reducing atmosphere for high thermal conductivity, which often results in deformation and warping, affecting electronic circuit densification and yield.
The development of an aluminum nitride sintered body with a thermal conductivity of 260 W/mK or more, achieved by sintering 90 to 99.5% by weight of aluminum nitride and 0.5 to 10% by weight of yttrium oxide, while reducing warpage through a specific manufacturing method involving a mixing step, molding, degreasing, deoxidation, sintering, and reduction calcination steps.
The method effectively achieves high thermal conductivity while significantly reducing warpage of the substrate, as evidenced by warpage indices C1, C2, and C3, and the thermal conductivity to warpage index ratio, which is 1400 to 2000, indicating improved compatibility and performance.
Smart Images

Figure 0007649399000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an aluminum nitride sintered body and a method for producing the same. [Background technology]
[0002] Aluminum nitride sintered products are made of insulating materials with high thermal conductivity and have been attracting attention as materials for high thermal conductive substrates. Due to their excellent thermal conductivity, the aluminum nitride sintered products are widely used as heat dissipation substrates for electronic components such as power transistor module substrates, light emitting diodes, IC packages, and laser diodes in semiconductors and electronic devices whose operation becomes unstable under high heat. In recent years, aluminum nitride sintered substrates have been widely used in electronic substrates for mobile applications, and higher heat dissipation properties are required. Therefore, various attempts have been made to improve the thermal conductivity of aluminum nitride sintered substrates.
[0003] For example, Patent Document 1 discloses an aluminum nitride sintered body and a method for producing the same. The aluminum nitride sintered body in Patent Document 1 has a high thermal conductivity of 260 W / m K or more by specifying the constituent components and content ratio of the grain boundary phase and the microstructure, specifically the average diameter, minimum diameter, maximum diameter, and number of aluminum nitride crystal grains. This method for producing an aluminum nitride sintered body is characterized by comprising a molding step of mixing aluminum nitride powder having an average particle size of 1.5 μm or less with a sintering aid containing at least a Y compound powder, and molding the mixture to obtain a molded body, a degreasing step of degreasing the molded body, a deoxidizing step of heat-treating the deoxidized molded body in a non-oxidizing atmosphere or a reduced pressure atmosphere at 1300°C to 1550°C to deoxidize it, a sintering step of heat-treating the deoxidized molded body in a non-oxidizing atmosphere at 1800°C to 1950°C to obtain a primary sintered body having a thermal conductivity of 230 W / m·K or more, and a reduction step of heat-treating the primary sintered body in a weakly reducing atmosphere at 1750°C to 1900°C to obtain a high thermal conductive aluminum nitride sintered body having a thermal conductivity of 260 W / m·K or more. In particular, in the sintering step, the deoxidized molded body is heat-treated in a non-oxidizing atmosphere at 1800°C to 1950°C to obtain a primary sintered body having a thermal conductivity of 230 W / m·K or more. In the subsequent reduction process, the primary sintered body is heat treated in a weakly reducing atmosphere at 1750°C to 1900°C to obtain an aluminum nitride sintered body with a thermal conductivity of 260 W / m K or more (high thermal conductive aluminum nitride sintered body). In this reduction process, the grain boundary phase, which is a factor that inhibits thermal conductivity, is precipitated on the surface and removed, resulting in an aluminum nitride sintered body with a thermal conductivity of 260 W / m K or more. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2011-37691 A Summary of the Invention [Problem to be solved by the invention]
[0005] Patent Document 1 provides an aluminum nitride sintered body having high thermal conductivity. In the conventional aluminum nitride sintered body as described in Patent Document 1, high-temperature firing under a reducing atmosphere is required to achieve high thermal conductivity, but it is known that the sintered body is likely to deform or warp under such conditions (see, for example, Comparative Examples 1, 2, and 9 in this specification). When the conventional aluminum nitride sintered body is incorporated into an electronic circuit as a substrate, the warping of the aluminum nitride sintered body substrate itself can adversely affect the densification of the circuit and the yield of the electronic circuit. Therefore, the inventors have set an object to reduce the warping of the substrate when the aluminum nitride sintered body is formed as a substrate while maintaining the high thermal conductivity property of the aluminum nitride sintered body.
[0006] The present invention has been made to solve the above-mentioned problems, and an object of the present invention is to provide an aluminum nitride sintered body having high thermal conductivity characteristics and reduced warping of the substrate, and a method for manufacturing the same. [Means for solving the problem]
[0007] (Section 1) An aluminum nitride sintered body according to one embodiment of the present invention is an aluminum nitride sintered body including aluminum nitride particles and a sintering aid phase, The thermal conductivity λ when converted to a thickness of 2.5 mm is 260 W / mK or more, and The warpage index value C1 indicating the warpage of the entire substrate area is less than 0.20 μm / mm; The warpage index value C1 is calculated by using a maximum height value Hmax (μm) and a minimum height value Hmin (μm) obtained by three-dimensional shape measurement of a square area of the entire surface of the substrate sample of the aluminum nitride sintered body, and a diagonal distance D1 (mm) of the square area, C1 = (Hmax-Hmin) / D1 It is characterized in that it is calculated by the following formula.
[0008] (Section 2) An aluminum nitride sintered body according to a further embodiment of the present invention is preferably the aluminum nitride sintered body according to item 1, characterized in that the warpage index value C1 is 0.14 to 0.19 μm / mm.
[0009] (Section 3) An aluminum nitride sintered body according to a further embodiment of the present invention is preferably the aluminum nitride sintered body according to item 1 or 2, wherein a second warpage index value C2 indicating warpage in a substrate corner region of the aluminum nitride sintered body is 0.17 to 0.35 μm / mm, The second warpage index value C2 is calculated by using a maximum height value Hmax (μm) and a minimum height value Hmin (μm) obtained by three-dimensional shape measurement of a square region including a corner of a surface of the substrate sample of the aluminum nitride sintered body, and a diagonal distance D2 (mm) of the square region, C2 = (Hmax-Hmin) / D2 It is characterized in that it is calculated by the following formula.
[0010] (Section 4) An aluminum nitride sintered body according to a further embodiment of the present invention is preferably the aluminum nitride sintered body according to any one of items 1 to 3, wherein a third warpage index value C3 indicating a warpage in a substrate central region of the aluminum nitride sintered body is 0.10 to 0.29 μm / mm, The third warpage index value C3 is calculated by using a maximum height value Hmax (μm) and a minimum height value Hmin (μm) obtained by three-dimensional shape measurement of a square region located at the center of the surface of the substrate sample of the aluminum nitride sintered body, and a diagonal distance D3 (mm) of the square region, C3 = (Hmax-Hmin) / D3 It is characterized in that it is calculated by the following formula.
[0011] (Section 5) An aluminum nitride sintered body according to a further embodiment of the present invention is preferably the aluminum nitride sintered body according to any one of items 1 to 4, characterized in that the thermal conductivity λ / warpage index value C1 is 1400 or more and 2000 or less.
[0012] (Section 6) An aluminum nitride sintered body according to a further embodiment of the present invention is preferably the aluminum nitride sintered body according to any one of items 1 to 5, characterized in that it is obtained by sintering 90 to 99.5% by weight of aluminum nitride and 0.5 to 10% by weight of yttrium oxide.
[0013] (Section 7) A method for producing an aluminum nitride sintered body according to one embodiment of the present invention includes the steps of: A method for producing an aluminum nitride sintered body according to any one of items 1 to 6, A mixing step of mixing an aluminum nitride raw material powder, a sintering aid, and an organic solvent to prepare a raw material mixture slurry; a molding step of molding the raw material mixture to obtain a molded body; a degreasing step of heating the molded body in a degreasing temperature range under a dry air inflow or a nitrogen atmosphere to perform a degreasing treatment; a deoxidation step of heating the degreased molded body in a deoxidation temperature range in a nitrogen atmosphere to perform a deoxidation treatment; a sintering step of sintering the deoxidized compact in a nitrogen atmosphere within a sintering temperature range to produce an aluminum nitride precursor sintered body; a reduction firing process in which an embedded structure is prepared by embedding at least a portion of the aluminum nitride precursor sintered body in aluminum nitride powder, and the embedded structure is heat-treated at 1850 to 1950°C in a weakly reducing atmosphere; a removing step of removing the aluminum nitride powder from the reduction-sintered embedded structure to obtain an aluminum nitride sintered body; Including, The reduction firing step is characterized in that it is carried out for 30 hours or more.
[0014] (Section 8) A further aspect of the method of the present invention, more preferably the method of item 7, is characterized in that the reduction and firing step includes placing the aluminum nitride precursor sintered body in a graphite container, or a BN container or an AlN container in which carbon black or a carbon sheet is placed, and embedding the aluminum nitride precursor sintered body in aluminum nitride powder until the aluminum nitride precursor sintered body is no longer visible. Effect of the Invention
[0015] The present invention provides an aluminum nitride sintered body that has a high thermal conductivity of 260 W / mK or more and reduces warping of the substrate. [Brief description of the drawings]
[0016] [Figure 1] FIG. 2 is a schematic diagram showing an example of a reduction firing step in one embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic diagram showing an example of a reduction firing step in conventional examples (Comparative Examples 1 and 2). [Diagram 3] FIG. 1 is a schematic diagram showing measurement ranges for warpage index values C1, C2, and C3 on the substrate surface of an aluminum nitride sintered body. [Figure 4] (a) Image showing visually the results of measuring the three-dimensional shape of the aluminum nitride sintered body substrate of Example 1 and (b) Comparative Example 1, where lighter colors indicate higher positions from the reference plane. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The aluminum nitride sintered body according to one embodiment of the present invention is formed into a substrate shape with a predetermined thickness and can be used as a circuit board for mounting electronic components. The aluminum nitride sintered body is made by sintering 90 to 99.5% by weight of aluminum nitride and 0.5 to 10% by weight of a sintering aid as main raw materials. The aluminum nitride sintered body is composed of a crystal phase of aluminum nitride particles and a liquid phase composed of a sintering aid phase.
[0018] The sintering aid may be selected from the group consisting of oxides of rare earth elements Y, La, Ce, Pr, Nd, Sm, Gd, Dy, Ho, Er, and Yb. In this embodiment, yttrium oxide (Y2O3) is used as the sintering aid. It is known that the addition of rare earth oxides as sintering aids can lower the liquid phase formation temperature during sintering and densify the crystal structure, resulting in a material that has both relatively high thermal conductivity and mechanical strength.
[0019] The aluminum nitride sintered body of this embodiment is characterized by having a thermal conductivity characteristic of 260 W / mK or more when converted to a thickness of 2.5 mm. In addition, the aluminum nitride sintered body preferably has a thermal conductivity characteristic of 240 W / mK or more when converted to a thickness of 0.5 mm. In the aluminum nitride sintered body of this embodiment, the Y2O3 content remaining in the sintered body is preferably 0.1% by weight or less, and the carbon (C element) content remaining in the sintered body is preferably 0.05% by weight or less. It is more preferable that the Y2O3 content is 0.03% by weight or less. It is more preferable that the carbon content is 0.03% by weight or less. The aluminum nitride sintered body of the present invention achieves both high thermal conductivity and reduced warpage of the substrate by controlling both the Y2O3 content and the carbon content remaining in the sintered body.
[0020] Moreover, the aluminum nitride sintered body can be configured as a substrate having a three-dimensional shape with less warping than conventional ones. In order to quantitatively evaluate the three-dimensional shape of this substrate, three-dimensional shape measurement can be performed by an optical measuring device having a camera optical system. The optical measuring device acquires three-dimensional data of the surface shape including unevenness, waviness, warping, etc. of the substrate surface by scanning a specified square area (a square range) of the substrate surface with high precision using (preferably two or more) camera optical systems. This three-dimensional data is a collection of height information (height value or z coordinate) at a measurement position (x, y coordinate) on a plane, and can be expressed as a three-dimensional map. The height value is a relative height with respect to a reference plane (H=0) automatically set by software as a plane on which the entire substrate surface is as horizontal as possible. The maximum height value Hmax is the maximum value of this relative height, and the minimum height value Hmin is the minimum value of the relative height. In order to evaluate the amount of warping of the substrate, the difference ΔH between the maximum height value Hmax and the minimum height value Hmin was used. It is considered that the larger the size of the square area to be measured, the larger the amount of warpage (ΔH) will be. Therefore, the warpage index value C was calculated by dividing the amount of warpage (ΔH) by the diagonal line D of the square area. The warpage index value C was then used to evaluate the warpage of the substrate. In this embodiment, the warpage index value C1 of the entire substrate area, the warpage index value C2 of the corner area, and the warpage index value C3 of the central area were evaluated. FIG. 3 is a schematic diagram showing the evaluation ranges of the warpage index values C1, C2, and C3. The surface roughness of the substrate itself is extremely small compared to the amount of warpage, and can be ignored.
[0021] The aluminum nitride sintered body has a warpage index value C1 of less than 0.20 μm / mm, which indicates the warpage of the entire substrate region. The warpage index value C1 is more preferably 0.14 to 0.19 μm / mm. Here, the warpage index value C1 is calculated by using the maximum height value Hmax (μm) and the minimum height value Hmin (μm) obtained by optically measuring the three-dimensional shape of a square region (a square range with one side of 50 mm) of the entire surface of a substrate sample of an aluminum nitride sintered body fabricated to a predetermined size (a square with a thickness of 0.5 mm and a side length of 50.8 mm), and the distance D1 (mm) of the diagonal of the square region, C1 = (Hmax-Hmin) / D1 It was calculated by:
[0022] The aluminum nitride sintered body has a second warpage index value C2 of 0.17 to 0.35 μm / mm, which indicates the warpage of the substrate corner region. Here, the second warpage index value C2 is calculated by using the maximum height value Hmax (μm) and the minimum height value Hmin (μm) obtained by optically measuring the three-dimensional shape of a square region (a square range with one side of 25 mm) including the corner of the surface of a substrate sample of the aluminum nitride sintered body fabricated to a predetermined size (a square with a thickness of 0.5 mm and a side length of 50.8 mm) and the diagonal distance D2 (mm) of the square region, C2 = (Hmax-Hmin) / D2 It was calculated by:
[0023] The aluminum nitride sintered body has a third warpage index value C3 of 0.10 to 0.29 μm / mm, which indicates the warpage in the substrate central region. Here, the third warpage index value C3 is calculated by using the maximum height value Hmax (μm) and the minimum height value Hmin (μm) obtained by three-dimensional shape measurement of a square region (a square range with one side of 25 mm) located at the center of the surface of a substrate sample of the aluminum nitride sintered body fabricated to a predetermined size (a square with a thickness of 0.5 mm and sides of 50.8 mm in this embodiment) and the diagonal distance D3 (mm) of the square region, C3 = (Hmax-Hmin) / D3 It was calculated by:
[0024] In the aluminum nitride sintered body produced by the conventional manufacturing method (Comparative Example 9), as described later, the first warpage index value C1 is about 0.30 μm / mm, the second warpage index value C2 is about 0.55 μm / mm, and the third warpage index value C3 is about 0.41 μm / mm, whereas the aluminum nitride sintered body of the present invention has the first warpage index value C1 of 0.14 to 0.19 μm / mm, the second warpage index value C2 of 0.17 to 0.35 μm / mm, and the third warpage index value C3 of 0.10 to 0.29 μm / mm. That is, in the aluminum nitride sintered body of the present invention, the warpage of the substrate is reduced in all of the substrate whole region, substrate corner region, and substrate center region, compared with the aluminum nitride sintered body produced by the conventional manufacturing method. Furthermore, the thermal conductivity λ / warpage index value C1 was used as an index showing compatibility between the first warpage index value C1 and the thermal conductivity λ. As described below, in the aluminum nitride sintered body produced by a conventional method (Comparative Example 9), λ / C1 is about 900, whereas in the aluminum nitride sintered body of the present invention, λ / C1 is 1400 to 2000. Therefore, the aluminum nitride sintered body of the present invention is characterized by having a high thermal conductivity of 260 W / mK or more, and by reducing warpage of the substrate compared to conventional products.
[0025] Next, a method for producing an aluminum nitride sintered body according to the present embodiment will be described. The method for producing an aluminum nitride sintered body mainly includes a mixing step of mixing an aluminum nitride raw material powder, a sintering aid, and an organic solvent to produce a slurry of the raw material mixture, a molding step of molding the raw material mixture to obtain a molded body, a degreasing step of heating the molded body in a degreasing temperature range under a dry air inflow or in a nitrogen atmosphere to perform a degreasing treatment, a deoxidizing step of heating the molded body after degreasing in a deoxidizing temperature range in a nitrogen atmosphere to perform a deoxidizing treatment, a sintering step of sintering the molded body after deoxidization in a sintering temperature range in a nitrogen atmosphere to produce an aluminum nitride precursor sintered body, a reduction firing step of embedding the aluminum nitride precursor sintered body with aluminum nitride powder to produce an embedded structure, and heat-treating the embedded structure at 1850 to 1950 ° C. for 30 hours or more in a weakly reducing atmosphere, and a removal step of removing the aluminum nitride powder from the embedded structure after reduction firing to obtain an aluminum nitride sintered body. Each step will be described in detail below. In this specification, "embedded" does not only mean that the aluminum nitride precursor sintered body is completely covered with aluminum nitride powder (the outer peripheral surface of the aluminum nitride precursor sintered body is completely surrounded by aluminum nitride powder), but also that the majority of the outer peripheral surface of the aluminum nitride precursor sintered body is covered with aluminum nitride powder to the extent that part of the outer peripheral surface is visible.
[0026] In the mixing step, an appropriate amount of aluminum nitride raw material powder and an appropriate amount of sintering aid powder are prepared. The aluminum nitride raw material powder, which is the main raw material, is preferably a high-purity fine powder with few metal impurities and low oxygen content. The sintering aid may be selected from the group of oxides of rare earth elements Y, La, Ce, Pr, Nd, Sm, Gd, Dy, Ho, Er, and Yb, and is preferably Y2O3. In the manufacturing method of this embodiment, 90 to 99.5% by weight of aluminum nitride raw material powder and 0.5 to 10% by weight of Y2O3 are mixed. The prepared raw materials (aluminum nitride and sintering aid) are put into a grinding mixer such as a ball mill, and an organic solvent, a dispersant, an organic binder, and / or a plasticizer are added, and the mixed material is sufficiently ground and mixed for a predetermined time. The organic solvent is, for example, a solvent prepared by mixing toluene and ethanol in a predetermined ratio. The amount of the organic solvent is about 30 to 70 parts by weight based on 100 parts by weight of the aluminum nitride raw material powder. The dispersant is, for example, a polycarboxylic acid surfactant. However, these organic solvents and dispersants can be selected arbitrarily. The organic binder is, for example, polyvinyl butyral resin or acrylic resin. The amount of the binder added is about 3 to 10 parts by weight based on 100 parts by weight of the raw material powder. The plasticizer is, for example, dibutyl phthalate (DBP). The amount of the binder added is about 1 to 5 parts by weight based on 100 parts by weight of the raw material powder. Then, a slurry-like raw material mixture in which each raw material is sufficiently dispersed and mixed is obtained. An additional additive may be added to the mixture of aluminum nitride raw material powder and sintering aid powder.
[0027] In the molding step, the obtained slurry-like raw material mixture is molded into a shape having a predetermined size and thickness by any means such as press molding, casting, doctor blade molding, etc., to produce a molded body.
[0028] In the degreasing step, the molded body is placed in a degreasing oven and heated for about 1 hour or more in a degreasing temperature range under an inflow of dry air or in a nitrogen atmosphere (although not limited to this), thereby removing organic components such as the added organic binder. The degreasing temperature range is preferably about 400 to 600°C (so as not to sinter the molded body). More preferably, the molded body is placed in a case made of BN (boron nitride) and heated for 4 hours at about 500°C under an inflow of dry air or heated for 4 hours at about 600°C in a nitrogen atmosphere, thereby properly degreasing the organic components.
[0029] In the deoxidation step, the degreased molded body is placed in a sintering furnace and heated in a nitrogen atmosphere in a deoxidation temperature range for 10 to 20 hours to deoxidize the molded body. The deoxidation temperature range is preferably 1500 to 1650° C. More preferably, the degreased molded body is placed inside a sealed BN case, and the case is placed in a sintering furnace for heat treatment.
[0030] In the sintering step, the deoxidized compact is heated and sintered in a sintering temperature range in a nitrogen atmosphere for 2 to 20 hours in a sintering furnace to produce an aluminum nitride precursor sintered body. The sintering temperature range is preferably 1750 to 1900°C. More preferably, the deoxidized compact is not removed from the sintering furnace, and the sintering step is carried out continuously. The produced aluminum nitride precursor sintered body is removed from the sintering furnace.
[0031] In the reduction firing step, as shown in FIG. 1, the aluminum nitride precursor sintered body is placed in a graphite (C) container, or a BN container or an AlN container in which carbon black or a carbon sheet is placed, and is completely embedded in aluminum nitride powder until the precursor sintered body is no longer visible, thereby producing an embedded structure made of aluminum nitride powder. At this time, it is preferable that all outer surfaces of the aluminum nitride precursor sintered body are surrounded by aluminum nitride powder. Then, the container containing the embedded structure is sealed, and the container is placed in a firing furnace. The aluminum nitride powder for embedding is preferably a powder with an oxygen content of 1% by weight or less. Thereafter, the material is heated at 1850 to 1950°C for 30 hours or more to perform reduction firing. The reduction firing time may be 30 hours or more, but is preferably 30 to 100 hours. At this time, graphite (carbon) or carbon black functions as a weak reducing atmosphere source, so that the inside of the firing furnace can be made into a weak reducing atmosphere. Nitrogen gas may be introduced in this reduction firing step. Alternatively, instead of introducing graphite (carbon) or carbon black, CO gas, which is a reducing gas, may be introduced to create a weakly reducing atmosphere.
[0032] FIG. 2 is a schematic diagram showing a conventional reduction firing process. In the conventional reduction firing process, an aluminum nitride precursor sintered body is placed in a graphite container and fired in a weakly reducing atmosphere to reduce the aluminum nitride precursor sintered body. As a result, the auxiliary component of the sintering aid is precipitated on the substrate surface and removed from the aluminum nitride precursor sintered body. However, in the conventional reduction firing process, the auxiliary component is discharged only by the atmosphere, which is inefficient, and it has been pointed out that the C component from the graphite container easily flows into the aluminum nitride precursor sintered body. In contrast, in the present invention, as shown in FIG. 1, the aluminum nitride precursor sintered body is reduced and fired in a state where it is embedded in aluminum nitride powder, so that the discharge amount of the auxiliary component and the inflow amount of the C component are more effectively controlled, and as a result, high thermal conductivity and reduced warpage of the substrate are achieved at the same time. In particular, in addition to the discharge of auxiliary components by controlling the atmosphere, the auxiliary components in the aluminum nitride precursor sintered body are adsorbed by the aluminum nitride powder, which further promotes the discharge of the auxiliary components. Also, since the aluminum nitride precursor sintered body does not directly contact the graphite container, the intrusion of carbon (C) components from the graphite container is suppressed. Therefore, although the aluminum nitride precursor sintered body is completely covered with aluminum nitride powder in FIG. 1, by covering the aluminum nitride precursor sintered body with aluminum nitride powder to the extent that the inflow of carbon (C) components can be suppressed, it is possible to achieve both high thermal conductivity and reduced warping of the substrate.
[0033] Finally, in the removal step, the aluminum nitride powder is removed from the embedded structure that has been reduction-sintered, thereby obtaining the aluminum nitride sintered body of the present invention.
[0034] Furthermore, when the aluminum nitride sintered body manufactured by the manufacturing method of this embodiment is identified by crystal phase identification using X-ray diffraction, it may have a diffraction peak of a rare earth compound (e.g., Y2O3, YAM, etc.) serving as a sintering aid in addition to a diffraction peak of the AlN crystal phase.
[0035] The present invention will be described in more detail below based on examples and comparative examples, but the present invention should not be construed as being limited to the following examples.
[0036] The aluminum nitride sintered bodies according to Examples 1 to 19 and Comparative Examples 1 to 9 were produced under the following conditions and procedures. Comparative Example 9 was produced under almost the same conditions as Example 1 of Patent Document 1.
[0037] A specified amount of aluminum nitride raw material powder and sintering aid powder were prepared. The aluminum nitride raw material powder used was manufactured by the reduction nitridation method, had an average particle size (D50) of about 1.0 μm, and contained less than 1% by weight of oxygen. The sintering aid used was Y2O3 powder with an average particle size (D50) of about 1.2 μm.
[0038] For Examples 1-7, 9-19 and Comparative Examples 1-9, a predetermined amount of Y2O3 powder, about 0.5 parts by weight of a dispersant, and about 60 parts by weight of a mixed solvent of toluene and ethanol were added to 100 parts by weight of aluminum nitride powder, and the mixture was ground and mixed by a ball mill using a resin container and alumina balls. 3.5 parts by weight of an acrylic binder was further added to the ground mixture as a binder, and the mixture was stirred and mixed by a ball mill until the dissolved binder solution and the ground mixture were completely mixed, and then a slurry was produced. Then, the raw material mixture was molded to a predetermined size and thickness by using a press molding method. Specifically, in the press molding method, the mixed and ground slurry was dried and granulated by a spray dryer to obtain AlN granules. Then, the AlN granules were press molded to obtain a substrate-like molded body having a predetermined size and thickness.
[0039] On the other hand, in Example 8, the steps from the mixing step to the molding step are different from those described above in order to form the material using a sheet forming method. A predetermined amount of Y2O3 powder, about 0.8 parts by weight of a surface-active dispersant, and about 25 parts by weight of a mixed solvent of toluene and ethanol were added to 100 parts by weight of aluminum nitride powder, and the mixture was ground and mixed by a ball mill using a resin container and alumina balls. A dissolved binder solution consisting of about 8 parts by weight of polyvinyl butyral as a binder, about 3.5 parts by weight of dibutyl phthalate as a plasticizer, and about 25 parts by weight of a mixed solvent of toluene and ethanol was added to the ground mixture. Then, the dissolved binder solution and the ground mixture were stirred and mixed by a ball mill until they were completely mixed, and then a slurry was prepared. Then, the slurry was heated and left in a vacuum to defoam and volatilize the solvent, and the viscosity at 25°C was adjusted to 20,000 cps. Next, a plate-shaped green sheet was obtained from the prepared slurry by a doctor blade method. The final drying temperature in the doctor blade molding device was set to 120° C. The obtained green sheet was cut into a predetermined size by die pressing to obtain a substrate-like molded product having a predetermined size and thickness.
[0040] Next, the produced molded body was placed in a BN case and heated in a nitrogen atmosphere at about 600°C for 4 hours to perform a degreasing process to remove organic components such as binders. The degreased molded body was placed on a BN bottom plate, and a BN side plate and top plate were attached to the bottom plate to assemble a closed case. The case containing the molded body was placed in a sintering furnace and heated in a nitrogen atmosphere at 1500 to 1650°C for 10 to 20 hours to perform a deoxidizing process for the molded body. For Examples 1 to 19 and Comparative Examples 1 to 4 and 6 to 9, the deoxidized molded body was not taken out of the sintering furnace, but was heated in a nitrogen atmosphere at 1750 to 1900°C for 2 to 20 hours to perform a sintering process for the molded body, thereby obtaining an aluminum nitride precursor sintered body. For Comparative Example 5, the sintering process was not performed, and the molded body was taken out of the sintering furnace and proceeded to the next reduction sintering process. For Comparative Example 6, the reduction sintering process was not performed, and the molded body was taken out of the sintering furnace to complete the process.
[0041] For Examples 1 to 19 and Comparative Examples 3 to 5, 7, and 8, the aluminum nitride precursor sintered body obtained was placed in a graphite container, or a BN container or an AlN container in which carbon black or a carbon sheet was placed, and was embedded in AlN powder for embedding until the aluminum nitride precursor sintered body was no longer visible, as shown in FIG. 1, and was sealed in the BN container or the AlN container. Aluminum nitride powder with an oxygen content of 1% by weight or less was used as the AlN powder for embedding in each example. Then, the sample was heated at 1780 to 1950°C for 5 to 100 hours and reduced and fired. In this way, samples for Examples 1 to 19 and Comparative Examples 3 to 5 were prepared. For Comparative Examples 1, 2, and 9, the aluminum nitride precursor sintered body obtained was placed in a graphite container or a BN container in which carbon black was placed, as shown in FIG. 2, and was sealed in the container. Then, the sample was heated at 1950°C for 70 hours in Comparative Examples 1 and 2, and at 1850°C for 12 hours in Example 9, and reduced and fired. In this manner, samples of Comparative Examples 1, 2, and 9 were prepared.
[0042] For each of the prepared samples of Examples 1 to 19 and Comparative Examples 1 to 9, the diffraction patterns obtained by X-ray diffraction measurement and the diffraction peaks of the AlN crystal phase were identified, thereby confirming that an aluminum nitride sintered body was obtained.
[0043] For each of the prepared samples of Examples 1 to 19 and Comparative Examples 1 to 9, various characteristic evaluations shown below were carried out.
[0044] (i) Thermal conductivity The aluminum nitride sintered body was cut into individual pieces measuring 10 mm × 10 mm × 0.5 mm thick, and a gold sputtering film of about 100 nm was formed on both sides of the individual pieces. Then, graphene was sprayed on both sides of the individual pieces to obtain a graphene coating amount of about 0.1 mg / mm. 2The samples were subjected to uniform blackening treatment so that the measured values were uniform. A thermal diffusivity measuring device (model LFA467) manufactured by Netsch Japan Co., Ltd. was used to perform measurements three times at a voltage of 250 V and a pulse width of 30 μs, and the average value was taken as the thermal diffusivity. The measured thermal diffusivity was multiplied by the density and specific heat of the sintered body measured by the Archimedes method to obtain the thermal conductivity of the 0.5 mm thick sample. In addition, aluminum nitride sintered bodies have the property that their thermal conductivity decreases when the temperature is high. The laser flash method is a measurement method that calculates the thermal diffusivity from the time it takes for the temperature of the sample to rise, and the measured value includes the decrease in thermal diffusivity due to the increase in the temperature of the sample. If measurements are taken with the same laser intensity, samples with a thinner thickness will have a larger increase in temperature than samples with a thicker thickness, and the thermal diffusivity will be measured as lower. Therefore, the table below shows the data obtained by measuring the thermal diffusivity of a sample with a thickness of 2.5 mmT, and then polishing it to thicknesses of 1.5, 1.0, 0.75, and 0.5 mmT for the same sample. According to Table 1, the thermal conductivity is clearly lower for samples with a thinner thickness. Using the obtained thermal conductivity, the multiplication factor for each thickness was calculated to convert it to a thickness of 2.5 mmT. Specifically, the thermal conductivity value of the sample with 0.5 mmT was multiplied by 1.10 to calculate the thermal conductivity λ converted to a thickness of 2.5 mmT. [Table 1]
[0045] (ii) Y2O3 content A scanning X-ray fluorescence analyzer, model "Primus IV" manufactured by Rigaku Corporation, was used. The aluminum nitride sintered body produced was cut into a size of 50.8 mm x 50.8 mm, and the Al and Y contents were measured at five points, the center and four corners of the substrate, and the Y2O3 content was calculated using a calibration curve, and the average value was taken as the Y2O3 content.
[0046] (iii) Carbon content The aluminum nitride sintered body thus produced was cut into a size of 50.8 mm x 50.8 mm, and a total of five points, namely the center and four corners of the substrate, were measured using an EMIA-Pro manufactured by Horiba, Ltd., using a high-frequency heating combustion-infrared absorption method in an oxygen stream, and the average value was taken as the carbon content.
[0047] (iv) Warpage index values C1, C2, C3 The 0.5 mm thick aluminum nitride sintered body substrate was cut to 50.8 mm x 50.8 mm, and a 50 mm square area, excluding the edge portion (0.4 mm), was optically scanned as a whole surface of the substrate using a one-shot 3D shape measuring instrument (model: VR-6000) manufactured by Keyence Corporation. The 3D shape was measured, and height value data and image data of the scanned area were obtained. In the image data, lighter colors visually indicate relatively higher positions. The warpage index values C1, C2, and C3 were calculated from the acquired data using an analysis application. First, in order to calculate the warpage index value C1, a reference plane was set (tilt correction) on the entire substrate surface, and then a surface measurement (flatness) was performed on the entire substrate surface, and the difference ΔH between the maximum height value Hmax and the minimum height value Hmin was calculated. The obtained difference ΔH was divided by the diagonal length (71.84 mm) of the 50.8 mm square area to calculate the warpage index value C1. Secondly, to calculate the warpage index value C2, a reference plane was set (tilt correction) over the entire surface of the substrate, and then surface measurements (flatness) were performed on each of the 25 mm square areas at the four corners of the substrate, and the average value of the difference between the maximum height value Hmax and the minimum height value Hmin was calculated, and the difference ΔH was calculated. The obtained difference ΔH was divided by the diagonal length (35.36 mm) of the 25 mm square area to calculate the warpage index value C2. Thirdly, to calculate the warpage index value C3, a reference plane was set (tilt correction) over the entire surface of the substrate, and then surface measurements (flatness) were performed on the 25 mm square area at the center of the substrate, and the difference ΔH between the maximum height value Hmax and the minimum height value Hmin was calculated. The obtained difference ΔH was divided by the diagonal length (35.36 mm) of the 25 mm square area to calculate the warpage index value C3.
[0048] Table 2 shows the conditions for each sample of Examples 1 to 19 and Reference Examples 1 to 9 and the results of various measurements regarding the properties of the sintered bodies.
[0049] [Table 2]
[0050] According to Table 2, in Examples 1 to 19 and Comparative Examples 1 and 2, the content of Y2O3 in the sintered body is 0.10% by weight or less, whereas in Comparative Examples 3 to 9, it is 0.4% by weight or more. In particular, in Examples 1 to 19, the content of Y2O3 in the sintered body is 0.03% by weight or less, whereas in Comparative Examples 1 and 2, the content of Y2O3 in the sintered body is 0.04% by weight or more, and in Comparative Examples 3, 7, and 8, it is 0.4% by weight or more. The content of Y2O3 in Examples 1 to 19, which were subjected to reduction firing for 30 hours or more under embedding conditions, is smaller than the content of Y2O3 in Comparative Examples 1 and 2, which were subjected to reduction firing for 70 hours without embedding. This shows that the auxiliary component in the sintered body is more effectively discharged to the outside by the embedding treatment with aluminum nitride powder and reduction firing for 30 hours or more, compared to reduction firing without embedding. In addition, when comparing the samples prepared under embedding conditions, the treatment time of the reduction firing step is 30 hours or more in Examples 1 to 19, whereas the treatment time of the reduction firing step is 20 hours or less (5, 10, 20 hours) in Comparative Examples 3, 7, and 8, but the Y2O3 contents are relatively high in Comparative Examples 3, 7, and 8. This indicates that the discharge of Y2O3 is insufficient with a treatment time of about 20 hours.
[0051] In addition, the carbon content in the sintered body was 0.03% by weight or less in Examples 1 to 19, whereas the carbon content in the sintered body was 0.08% by weight or more in Comparative Examples 1 and 2. This shows that the inflow of carbon into the sintered body was suppressed by embedding the precursor sintered body in aluminum nitride powder and reducing and firing it.
[0052] That is, as shown in Table 2, in Examples 1 to 19, the Y2O3 content in the sintered body was controlled to 0.10% by weight or less, and the carbon content in the sintered body was controlled to 0.05% by weight or less.
[0053] According to Table 2, in Examples 1 to 19 and Comparative Examples 1, 2, 8, and 9, the thermal conductivity λ (2.5T conversion) is high, at 260 W / mK or more, whereas in Comparative Examples 3 to 6, the thermal conductivity λ (2.5T conversion) is less than 250 W / mK. Since Comparative Examples 3, 4, and 6 did not undergo an appropriate reduction firing process, it can be said that the auxiliary components were not sufficiently discharged. Specifically, in Comparative Example 3, the processing time of the reduction firing process is short, and in Comparative Example 4, the processing temperature of the reduction firing process is low. Comparative Example 6 did not undergo the reduction firing process. Moreover, Comparative Example 5 did not undergo a sintering process.
[0054] Next, the warpage characteristics of the sintered bodies of the examples and the comparative examples will be described. FIG. 4 is an image visually showing the three-dimensional shape measurement results of the aluminum nitride sintered body substrate, with FIG. 4(a) being an image of the example 1 and FIG. 4(b) being an image of the comparative example 1. In the shading of the image, the lighter the color, the higher the position from the reference surface. Comparing FIG. 4(a) and FIG. 4(b), it can be visually confirmed that the shading is more uniform in the example 1 than in the comparative example 1, and the height difference of the substrate surface is smaller (the warpage is smaller). Then, the warpage of the substrate was quantitatively evaluated by analyzing the data related to the image.
[0055] Table 3 shows the conditions for each sample of Examples 1 to 19 and Comparative Examples 1 to 9, as well as various measurement results regarding the warpage characteristics and thermal conductivity characteristics of the sintered bodies.
[0056] [Table 3]
[0057] In Examples 1 to 19 and Comparative Example 6, the warpage index value C1 is less than 0.20 μm / mm, whereas in Comparative Examples 1 to 5 and 7 to 9, the warpage index value C1 is 0.22 μm / mm or more. In particular, in Examples 1 to 19, the warpage index value C1 is 0.14 to 0.19 μm / mm. In Comparative Example 6, the warpage index value C1 is less than 0.20 μm / mm because the reduction firing process was not performed. However, in Comparative Example 6, the thermal conductivity λ is less than 260 W / mK, and high thermal conductivity and reduced warpage of the substrate cannot be achieved at the same time. On the other hand, in Comparative Examples 1, 2, and 9, the warpage index value C1 is relatively large due to the reduction firing process without embedding. In Comparative Examples 3, 7, and 8, the processing time of the reduction firing process under embedding is short (less than 30 hours) compared to the Examples, so the warpage index value C1 is relatively large. In Comparative Example 4, the treatment temperature of the reduction firing step under embedding is low (less than 1850° C.), and therefore the warpage index value C1 is relatively large compared to the Examples.
[0058] In Examples 1 to 19 and Comparative Example 6, the warpage index value C2 is less than 0.40 μm / mm, whereas in Comparative Examples 1 to 5 and 7 to 9, the warpage index value C2 is 0.41 μm / mm or more. In particular, in Examples 1 to 19, the warpage index value C2 is 0.17 to 0.35 μm / mm. In Comparative Example 6, the warpage index value C2 is less than 0.40 μm / mm because the reduction firing process was not performed. However, in Comparative Example 6, the thermal conductivity λ is less than 260 W / mK, and high thermal conductivity and reduced warpage of the substrate cannot be achieved at the same time. On the other hand, in Comparative Examples 1 and 2, the warpage index value C2 is relatively large due to the reduction firing process without embedding. In Comparative Examples 3, 7, and 8, the processing time of the reduction firing process under embedding is short (less than 30 hours) compared to the Examples, so the warpage index value C2 is relatively large. In Comparative Example 4, the treatment temperature of the reduction firing step under embedding is low (less than 1850° C.), and therefore the warpage index value C2 is relatively large compared to the Examples.
[0059] In Examples 1 to 19 and Comparative Example 6, the warpage index value C3 is less than 0.35 μm / mm, whereas in Comparative Examples 1 to 5 and 7 to 9, the warpage index value C3 is 0.37 μm / mm or more. In particular, in Examples 1 to 19, the warpage index value C3 is 0.10 to 0.29 μm / mm. In Comparative Example 6, the warpage index value C3 is less than 0.35 μm / mm because the reduction firing process was not performed. However, in Comparative Example 6, the thermal conductivity λ is less than 260 W / mK, and high thermal conductivity and reduced warpage of the substrate cannot be achieved at the same time. On the other hand, in Comparative Examples 1 and 2, the warpage index value C3 is relatively large due to the reduction firing process without embedding. In Comparative Examples 3, 7, and 8, the processing time of the reduction firing process under embedding is short (less than 30 hours) compared to the Examples, so the warpage index value C3 is relatively large. In Comparative Example 4, the treatment temperature of the reduction firing step under embedding is low (less than 1850° C.), and therefore the warpage index value C3 is relatively large compared to the Examples.
[0060] In order to evaluate the relationship between thermal conductivity and warpage of the substrate, λ / C1 was calculated for each sample. In Examples 1 to 19, λ / C1 was 1300 or more, whereas in Comparative Examples 1 to 9, it was less than 1220. In particular, in Examples 1 to 19, λ / C1 was 1400 to 2000. That is, Examples 1 to 19 achieve both high thermal conductivity of 260 W / mK or more and reduced warpage of the substrate.
[0061] The present invention is not limited to the above-described embodiment, and can be embodied in various forms within the technical scope of the present invention.
Claims
1. An aluminum nitride sintered body comprising aluminum nitride particles and a sintering aid phase, The thermal conductivity λ when converted to a thickness of 2.5 mm is 260 W / mK or more, and The warpage index value C1 indicating the warpage of the entire substrate region is less than 0.20 μm / mm; The warpage index value C1 is calculated by using a maximum height value Hmax (μm) and a minimum height value Hmin (μm) obtained by three-dimensional shape measurement of a square region of the entire surface of the substrate sample of the aluminum nitride sintered body, and a diagonal distance D1 (mm) of the square region, C1=(Hmax-Hmin) / D1 An aluminum nitride sintered body, characterized in that the alumina content is calculated by the following formula:
2. 2. The aluminum nitride sintered body according to claim 1, wherein the warpage index value C1 is 0.14 to 0.19 μm / mm.
3. a second warpage index value C2 indicating the warpage of the substrate corner region of the aluminum nitride sintered body is 0.17 to 0.35 μm / mm; The second warpage index value C2 is calculated by using a maximum height value Hmax (μm) and a minimum height value Hmin (μm) obtained by three-dimensional shape measurement of a square region including a corner of a surface of the substrate sample of the aluminum nitride sintered body, and a diagonal distance D2 (mm) of the square region, C2=(Hmax-Hmin) / D2 2. The aluminum nitride sintered body according to claim 1, wherein the aluminum nitride sintered body is calculated by the following formula:
4. a third warpage index value C3 indicating the warpage of the substrate central region of the aluminum nitride sintered body is 0.10 to 0.29 μm / mm; The third warpage index value C3 is calculated by using a maximum height value Hmax (μm) and a minimum height value Hmin (μm) obtained by three-dimensional shape measurement of a square region located at the center of the surface of the substrate sample of the aluminum nitride sintered body, and a diagonal distance D3 (mm) of the square region, C3=(Hmax-Hmin) / D3 2. The aluminum nitride sintered body according to claim 1, wherein the aluminum nitride sintered body is calculated by the following formula:
5. 2. The aluminum nitride sintered body according to claim 1, characterized in that the thermal conductivity λ / warpage index value C1 is 1,400 or more and 2,000 or less.
6. 2. The aluminum nitride sintered body according to claim 1, which is obtained by sintering 90 to 99.5% by weight of aluminum nitride and 0.5 to 10% by weight of yttrium oxide.
7. A method for producing the aluminum nitride sintered body according to any one of claims 1 to 6, comprising the steps of: A mixing step of mixing an aluminum nitride raw material powder, a sintering aid, and an organic solvent to prepare a raw material mixture slurry; a molding step of molding the raw material mixture to obtain a molded body; a degreasing step of heating the molded body in a degreasing temperature range under a dry air inflow or in a nitrogen atmosphere to perform a degreasing treatment; a deoxidation step of heating the degreased molded body in a deoxidation temperature range in a nitrogen atmosphere to perform a deoxidation treatment; a sintering step of sintering the deoxidized compact in a nitrogen atmosphere within a sintering temperature range to produce an aluminum nitride precursor sintered body; a reduction firing step of preparing an embedded structure by embedding at least a portion of the aluminum nitride precursor sintered body with aluminum nitride powder, and heat treating the embedded structure at 1850 to 1950° C. in a weakly reducing atmosphere; a removing step of removing the aluminum nitride powder from the reduction-sintered embedded structure to obtain an aluminum nitride sintered body; Including, A method for producing an aluminum nitride sintered body, characterized in that the reduction firing step is carried out for 30 hours or more.
8. The method according to claim 7, characterized in that the reduction and firing step includes placing the aluminum nitride precursor sintered body in a graphite container, or a BN container or an AlN container in which carbon black or a carbon sheet is placed, and embedding the aluminum nitride precursor sintered body in aluminum nitride powder until the aluminum nitride precursor sintered body is no longer visible.
Citation Information
Patent Citations
Green body and sintered body of aln powder, and their production
JP1999322432A
Aluminum nitride sintered compact and its producing process
JP2004083341A
Highly heat-conductive aluminum nitride sintered compact, substrate using this, circuit board, semiconductor device, and method for manufacturing highly heat-conductive aluminum nitride sintered compact
JP2011037691A
Heat dissipation plate for semiconductor device
JP2012116750A
Aluminum nitride sintered substrate and method for manufacturing the same
JP2013203597A